2013
DOI: 10.1111/sji.12027
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐induced Changes in Mannan‐binding Lectin Levels and Complement Activation in a Mouse Model of Type 1 Diabetes

Abstract: Circulating mannan-binding lectin (MBL) levels are elevated in type 1 diabetes. Further, high MBL levels are associated with the development of diabetic nephropathy. In animals, a direct effect of MBL on diabetic kidney changes is observed. We hypothesized that MBL levels and detrimental complement activation increase as a consequence of diabetes. We measured plasma MBL before and 7 weeks after inducing diabetes by streptozotocin. Mice have two MBLs, MBL-A and MBL-C. Diabetes induction led to an increase in MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
(45 reference statements)
4
19
0
1
Order By: Relevance
“…The positive correlation between HbA 1c and MBL concentrations in the current study supports that the MBL concentration in humans increases within a given genotype as a consequence of diabetes in agreement with animal studies (14).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The positive correlation between HbA 1c and MBL concentrations in the current study supports that the MBL concentration in humans increases within a given genotype as a consequence of diabetes in agreement with animal studies (14).…”
Section: Discussionsupporting
confidence: 77%
“…However, MBL concentrations are higher in patients with diabetes than in healthy subjects, despite similar MBL2 genotype distribution (2,6,12,13). Animal studies suggest this to be explained by a secondary increase in MBL concentration after diabetes induction (14). Finally, we recently showed that H-ficolin, another complement-activating pattern-recognition molecule, is also associated with development of diabetic kidney changes (15).…”
mentioning
confidence: 99%
“…[13] WORLD JOURNAL OF PHARMACY AND PHARMACEUTICAL SCIENCES The increase in MBL-Complement was associated with the increasing plasma glucose levels. [1] MBL levels increase after induction of diabetes and in parallel with increasing plasma glucose. [1] Elevated MBL level in T1DM…”
Section: Introductionmentioning
confidence: 99%
“…[1] MBL levels increase after induction of diabetes and in parallel with increasing plasma glucose. [1] Elevated MBL level in T1DM…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation